Advantages and Limitations of Current Techniques for Analyzing the Biodistribution of Nanoparticles - Arms, Lauren; Smith, Doug W.; Flynn, Jamie; Palmer, William; Martin, Antony; Woldu, Ameha; Hua, Susan (Frontiers in Pharmacology, 2018)
Nanomedicines are typically submicrometer-sized carrier materials (nanoparticles) encapsulating therapeutic and/or imaging compounds that are used for the prevention, diagnosis and treatment of diseases. They are increasingly being used to overcome biological barriers in the body to improve the way we deliver compounds to specific tissues and organs. Nanomedicine technology aims to improve the balance between the efficacy and the toxicity of therapeutic compounds. Nanoparticles, one of the key technologies of nanomedicine, can exhibit a combination of physical, chemical and biological characteristics that determine their in vivo behavior. A key component in the translational assessment of nanomedicines is determining the biodistribution of the nanoparticles following in vivo administration in animals and humans. There are a range of techniques available for evaluating nanoparticle biodistribution, including histology, electron microscopy, liquid scintillation counting (LSC), indirectly measuring drug concentrations, in vivo optical imaging, computed tomography (CT), magnetic resonance imaging (MRI), and nuclear medicine imaging. Each technique has its own advantages and limitations, as well as capabilities for assessing real-time, whole-organ and cellular accumulation. This review will address the principles and methodology of each technique and their advantages and limitations for evaluating in vivo biodistribution of nanoparticles.